2022
DOI: 10.1186/s40001-022-00691-2
|View full text |Cite
|
Sign up to set email alerts
|

Ischemic stroke and intestinal flora: an insight into brain–gut axis

Abstract: Stroke is a type of cerebrovascular disease that significantly endangers human health and lowers quality of life. This understandably places a heavy burden on society and families. In recent years, intestinal flora has attracted increasing attention from scholars worldwide, and its association with ischemic stroke is becoming a hot topic of research amongst researchers in field of stroke. After suffering from a stroke, intestinal microbial dysbiosis leads to increased intestinal permeability and activation of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(19 citation statements)
references
References 139 publications
(118 reference statements)
1
18
0
Order By: Relevance
“…Nevertheless, the relationship between Ber and neuroinflammation induced by ICH is poorly understood, and exploring this relationship may provide a new direction for ICH treatment. In recent years, studies have reported an increase in intestinal barrier permeability after ICH [31], which can lead to microglia activation through inter-organ communication with intestinal-derived proinflammatory cytokine [32,33]. In our study, we found that the expression of the tight junction proteins Occludin and ZO-1 was reduced after ICH, and that Ber treatment could ameliorate the disruption of the gut barrier.…”
Section: Discussionsupporting
confidence: 66%
“…Nevertheless, the relationship between Ber and neuroinflammation induced by ICH is poorly understood, and exploring this relationship may provide a new direction for ICH treatment. In recent years, studies have reported an increase in intestinal barrier permeability after ICH [31], which can lead to microglia activation through inter-organ communication with intestinal-derived proinflammatory cytokine [32,33]. In our study, we found that the expression of the tight junction proteins Occludin and ZO-1 was reduced after ICH, and that Ber treatment could ameliorate the disruption of the gut barrier.…”
Section: Discussionsupporting
confidence: 66%
“…The intestinal flora is essential for maintaining host health by regulating cellular activity and the immune system. According to previous studies, it is associated with leukemia infection [ 56 ], small bowel colitis [ 57 ], ischemic stroke [ 58 ], obesity [ 59 ], and a number of other harmful conditions.…”
Section: Physiological Activity and Product Development Of Polysaccha...mentioning
confidence: 99%
“…On the other hand, glucocorticoids released by HPA during the body's inflammatory response can regulate excessive immunity [8]; (3) Immune system: hypoxia-ischemia causes abnormal immune signal release and communication, which may lead to the imbalance of peripheral system homeostasis through the two-way feedback of brain-gut circulation, aggravating the outcome of cerebral infarction [9]; (4) Microbiota-derived neuroactive compounds, such as trimethylamine positive oxide (TMAO), short-chain fatty acids, lipopolysaccharide (LPS) and other complex pathways, undergo bacterial translocation [10]. Other scholars have found that after stroke caused by inflammatory response after the activation of the intestinal immune system will further lead to the body bacteria translocation, based on blood brain barrier damage will increase local brain tissue inflammation response, but at the same time some of the intestinal flora metabolites can inhibit inflammation after a stroke and promote restoration of the nerve function to alleviate ischemia-reperfusion injury [11]. At present, brain-gut axis is a hot research field in biology and medicine in recent years.…”
Section: Microbial-gut-brain Axis Pathwaymentioning
confidence: 99%